PENGAWASAN KINERJA PEGAWAI DI KANTOR KECAMATAN BANGGAI KABUPATEN BANGGAI LAUT (Studi Tentang Pengawasan Camat Terhadap Kinerja Aparatur Di Kecamatan Banggai) - Sandewa, Fadli (Katalogis, 2017)
This research aims to analyse the Monitoring Performance of Officials at Subdistrict Office of Banggai Laut. This research used 5 informans. They were the secretary of subdistrict head, the officials at subdistrict office, Dodung headman, and community leader. The researcher used purposive technique in choosing the informan. The researcher choosed the informan purposely. The researcher used observation,interview,and documentation as a technique in collecting data. The research result showed that the monitoring performance of officials at subdistrict office of Banggai Laut was not effective. It was proved by the two indicators used, direct monitoring and indirect monitoring. The direct monitoring which was done by the subdistrict head showed that the officials performance was not optimal, as well as the indirect monitoring could not be said run well because there were some officials who had not been able to work with the maximum due to the lack of monitoring by the subdistrict head. Moreover, many of officials did not understand their duties as civil servants well. Public opinions also gave big impact. Public assumed that the subdistrict head performance was less than maximum because the decision-making by the subdistrict head gave less positive impact on society.Â